2002
DOI: 10.1046/j.1526-4637.2002.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Masses Associated with Intrathecal Drug Infusion: A Review of Preclinical Evidence and Human Data

Abstract: Objectives. The phenomenon of inflammatory masses at the tips of intrathecal drug administration catheters was the subject of a recent case-compilation report and a number of animal studies. We sought to synthesize current clinical and preclinical data to formulate hypotheses about the etiology of catheter-tip masses.Methods. We reviewed the published human clinical data, new unpublished clinical data, and the results of preclinical studies in two mammalian species, beagle dogs and sheep.Results. Intrathecal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
171
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(177 citation statements)
references
References 40 publications
4
171
0
2
Order By: Relevance
“…In fact, morphine has the potential to induce the release of these proinflammatory cytokines directly: glial cells express opioid receptors (Maderspach and Solomonia, 1988) and chronic opioid treatment can induce the naloxone-reversible release of IL-1 from mixed brain cell cultures (Das et al, 1995). Thus, intriguing parallels may be found to recent clinical reports that long-term and/or high-dose intrathecal morphine administration is associated with the invasion of spinal tissue with immune cells and development of inflammatory masses at the catheter tip (for review, see Yaksh et al, 2002). Thus, in addition to evidence for glial inflammatory processes induced by shorterterm and lower-dose intrathecal morphine provided by the present study, intrathecal morphine has the capability of altering the function of immune cells as well.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, morphine has the potential to induce the release of these proinflammatory cytokines directly: glial cells express opioid receptors (Maderspach and Solomonia, 1988) and chronic opioid treatment can induce the naloxone-reversible release of IL-1 from mixed brain cell cultures (Das et al, 1995). Thus, intriguing parallels may be found to recent clinical reports that long-term and/or high-dose intrathecal morphine administration is associated with the invasion of spinal tissue with immune cells and development of inflammatory masses at the catheter tip (for review, see Yaksh et al, 2002). Thus, in addition to evidence for glial inflammatory processes induced by shorterterm and lower-dose intrathecal morphine provided by the present study, intrathecal morphine has the capability of altering the function of immune cells as well.…”
Section: Discussionmentioning
confidence: 97%
“…Hypotheses that could explain the formation of catheter tip inflammatory masses, such as foreignbody reaction to silicone and other catheter material, infection, catheter-tip design, and the infusate-especially opioid analgetics, have been proposed [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Drug concentration and dose are supposed to be potential causative factors in the formation of catheter-associated masses [9,10]. A strong evidence that inflammatory masses at the catheter tips are caused by highly concentrated morphine infusate was identified by Yaksh et al [11] in animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This use of high concentrations in human pumps has led to local toxicity. For opiates, the manifestation of this toxicity is the intrathecal granuloma [37, 116,[461][462][463]. Our group showed that the primary determinant for intrathecal opiate granulomas is the local concentration to which the tissue adjacent to the catheter tip is exposed [49, 51, 52].…”
Section: Drug Dosingmentioning
confidence: 99%